The Metaverse as a Transcomplex Scenario of Technoeducation (Docentes 2.0 Journal, 2022)
In the digital age, the educational field has undergone significant transformations, which invites all those involved in the teaching-learning phase to reflect on the challenges involved in technological literacy. The purpose of this essay was to consider the challenges involved in transcomplexity in the face of technological literacy with the arrival of the metaverse in the classroom. Documentary research was carried out under the bibliographic method, supported by the humanistic paradigm, with a qualitative approach, exploratory-interpretative type, documentary design, reading technique and search tool, organization, and information analysis. After two years of confinement, the educational process remains utopian in the face of a technological world, full of discrepancies, archetypes, contradictions, and challenges to the global difficulties present in humanity. It is essential to strengthen the educational system to understand the change of the archetype before the prevailing bases are subjected to the erroneous dogma that technology will replace them or is their greatest enemy. Unquestionably, the epidemic has promoted the vision of a world of possibilities to evaluate, re-evaluate and give new meaning to reality in the training process. Therefore, it is necessary to balance epistemological, ontological, teleological, axiological, and methodological beliefs to generate a new dialogue in interconnected educational praxis where transcendence is promoted, to reach a higher level of knowledge, under an immanent introspective look of the human being in digital education.
Keywords: Agogical Sciences; transcomplexity; metaverse; technoeducation; praxis